VALIDASI METODE ANALISA PENETAPAN KADAR EPIGALOKATEKIN GALAT DENGAN KLT DENSITOMETRI - Nining Sugihartini; Achmad Fudholi; Suwidjiyo Pramono; Sismindari Sismindari (Pharmaciana, 2012)
TLC Densitometry is one of method which was used to measure amount of activesubstance. Active substance of epigallocathechin gallate is one of in green tea extractcream. Method of analysis must be validated to prove that method will give the dataclose with the real value. Aim of this research is to prove that TLC Densitometry methodhave liniearity, precision and accuration that fulfill the requirement. This study usedconcentration 600, 1800 and 3000 ug/ml with 3 replications to measure precision(based on value of CV) and accuration (based on value of recovery). Liniearity wasknown based on value of r of curve regression between concentration and wide area ofchromatogram. LOD and LOQ was calculated based on curve regression. Researchshowed that method of analyse had liniearity with r= 0,98. Value of CV concentrationof 600, 1800 and 3000 ug/ml were 8,18%; 3,19% and 1,53%, respectively and recoverywere 88,10%; 99,65% dan 111,33%, respectively. Value of LOD was 827,01 Âµg/ml andLOQ was 2756,69 Âµg/ml.